2012
DOI: 10.1248/bpb.b212019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Intracellular Defense Factors against Methylmercury Toxicity

Abstract: Methylmercury (MeHg) is a causative agent of Minamata disease and an environmental pollutant that comprises a large portion of organically occurring mercury. Many aspects of the biological defense mechanisms against MeHg toxicity remain unclear. Recently, nuclear factor-E2-related factor 2 (Nrf2), heat shock factor protein 1 (Hsf1), and hydrogen sulfide were identified as intracellular defense factors against MeHg toxicity. These findings suggest that novel biological defense mechanisms against MeHg toxicity e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Under stress condition, Nrf2 dissociates from Keap1 and translocates into the nuclear where it binds to antioxidant responsive element (ARE), leading to the expression of its target genes [ 4 ]. These include many cytoprotective proteins and drug efflux transporters, such as heme oxygenase 1 (HO-1), NAD (P) H: quinone oxidoreductase (NQO1), glutamate cysteine ligase (GCL), and multidrug resistance-associated protein 2 (MRP2) [ 5 , 6 ]. Nrf2 pathway is considered as an important endogenous antioxidant signaling pathway and increasing number of studies suggested the potential role of Nrf2 as a therapeutic target to prevent liver injury caused by oxidative stress [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Under stress condition, Nrf2 dissociates from Keap1 and translocates into the nuclear where it binds to antioxidant responsive element (ARE), leading to the expression of its target genes [ 4 ]. These include many cytoprotective proteins and drug efflux transporters, such as heme oxygenase 1 (HO-1), NAD (P) H: quinone oxidoreductase (NQO1), glutamate cysteine ligase (GCL), and multidrug resistance-associated protein 2 (MRP2) [ 5 , 6 ]. Nrf2 pathway is considered as an important endogenous antioxidant signaling pathway and increasing number of studies suggested the potential role of Nrf2 as a therapeutic target to prevent liver injury caused by oxidative stress [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Up-regulation of heat shock proteins are associated with protective stress responses to minimize cell protein damage [40], [41], [64]. Methylmercury exposure in birds is associated with oxidative stress in liver, kidney, and brain tissue [65], and up-regulation of heat shock proteins has recently been identified as a potential biological defense mechanism against MeHg toxicity [66], [67]. However, it is unclear what the consequences are for down-regulation of heat shock proteins as we observed with egrets.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear factor‐E2‐related factor 2 (Nrf2), bounding to Kelch‐like epichlorohydrin‐associated protein 1 (Keap1) in the cytoplasm, is a key regulator in cellular defenses against oxidative stress . Once activated, Nrf2 is translocated into the cell nucleus and binds to antioxidant response elements (AREs) located in the regulatory regions of many responsible genes for cellular defense such as glutamate cysteine ligase (GCL), heme oxygenase‐1 (HO‐1), and phase‐II detoxifying enzymes . However, the protective mechanisms of Nrf2 signaling pathway against MeHg toxicity have not been clearly understood.…”
Section: Introductionmentioning
confidence: 99%